Building an entrepreneurial Caribbean university library: practice, possibilities, and lessons. Issue 1 (April 2022) - Harris, Sasekea; ,
Purpose: Entrepreneurship is being seen as a core driver of economic revival. Consequently, organizations and institutions, including universities, are being called upon to accelerate their role in an increasingly entrepreneurial environment. The sub-streams of entrepreneurship are manifold; yet, there is still the notion that entrepreneurship is solely about making profits. Within this context there are questions, within and without librarianship, regarding whether a library, which is a non-profit entity, can be an entrepreneur. As such, this paper purposed to examine the extent to which the terms library and entrepreneurship harmonise, through a case study of a large Caribbean university library, with the objective of highlighting practice, possibilities and lessons. Design/Methodology: Employees of the understudy library were purposively sampled and surveyed. Findings: The theo-practical lens through which one views entrepreneurship, determine perceptions regarding the status of the understudy library as an entrepreneur. Research Limitations/Implications: This paper examined one of the largest indigenous university library in the English-speaking Caribbean; it is possible that the situation for other types/sizes of Caribbean university libraries may vary. Therefore, it would be useful to study other Caribbean university libraries. Originality/Value: This paper contributes to the growing body of literature on "libraries and entrepreneurship" and evidence for "value of libraries" albeit from a Caribbean perspective. It also highlights the status of entrepreneurship in libraries in general, and a Caribbean university library in particular, and in this regard offers a case for strengthening entrepreneurship in other Caribbean university libraries. Additionally, it is the first scholarly paper on Caribbean university library entrepreneurship. Practical & Social Implications: There is a gap in the literature on practical examples and scholarly papers on building a Caribbean entrepreneurial university library. Using the response of the understudy Caribbean university library, this paper seeks to fill this gap, albeit incrementally, through proposing a broad "Entrepreneurial University Library Framework for building an entrepreneurial university library within the context of the Caribbean. Although this study was conducted within a Caribbean context, hence the phrase entrepreneurial Caribbean university library, its model can be used by other comparable institutions worldwide, struggling with increasing demands to be entrepreneurial.